1976
DOI: 10.1115/1.3423927
|View full text |Cite
|
Sign up to set email alerts
|

The Energy Stability Limit for Flow in a Curved Channel

Abstract: The energy stability limit is calculated for flow in a curved channel due to a pressure gradient acting around the channel. The energy limit is found among transverse disturbances and is of the same order for all channel radius ratios. The difference between the previously available linear limit and the energy limit increases dramatically as the instability mechanism changes, with radius ratio, from centrifugal force to viscosity in the limiting plane Poiseuille flow case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
1988
1988

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…They found that when 0.95 < 7 < (1 -2.179 x axisymmetric disturbances are more unstable Instability and transition in curved channel $ow 41 9 than two-dimensional TS modes, but for 7 > (1 -2.179 x the reverse is true. For wide gaps, Jankowski & Takeuchi (1976) indicate that axisymmetric disturbances are the most unstable. Daudpota, Zang & Hall (1987) obtain weakly nonlinear solutions for TS waves, Dean vortices and mixed modes for 7 z 2.179 x lop5.…”
Section: Introductionmentioning
confidence: 99%
“…They found that when 0.95 < 7 < (1 -2.179 x axisymmetric disturbances are more unstable Instability and transition in curved channel $ow 41 9 than two-dimensional TS modes, but for 7 > (1 -2.179 x the reverse is true. For wide gaps, Jankowski & Takeuchi (1976) indicate that axisymmetric disturbances are the most unstable. Daudpota, Zang & Hall (1987) obtain weakly nonlinear solutions for TS waves, Dean vortices and mixed modes for 7 z 2.179 x lop5.…”
Section: Introductionmentioning
confidence: 99%